Vertical- vs. horizontal-oriented drop jump training: Chronic effects on explosive performances of elite handball players - Dello Lacono, A.; Martone, D.; Milic, M.; Padulo, J. (The Journal of Strength and Conditioning Research, 2017)
This study aimed to assess the chronic effects of vertical drop jump (VDJ)- and horizontal drop jump (HDJ)-based protocols on neuromuscular explosive abilities, such as jumping, sprinting, and changes of direction (COD). Eighteen elite male handball players (age 23.4 ± 4.6 years, height 192.5 ± 3.7 cm, weight 87.8 ± 7.4 kg) were assigned to either VDJ or HDJ group training twice a week for 10 weeks. Participants performed 5-8 sets × 6-10 repetitions of vertical alternate (VDJ) or horizontal alternate (HDJ) 1-leg drop jumps, landing from the top of a platform 25 cm in height. Before and after training, several performance, kinetic, and kinematic variables were assessed. The HDJ led to greater improvement of the sprint time (-8.5% vs. -4%, p = 0.05) and COD performance in comparison with the VDJ (-7.9% vs. -1.1%, p = 0.05), whereas the VDJ caused greater improvement in the vertical jump compared with the HDJ (+8.6% vs. +4.1%, p = 0.05). Moreover, the VDJ regimen compared with the HDJ induced greater changes in the kinetic variables associated with vertical jumping performance, such as peak ground reaction forces (+10.3% vs. +4.3%), relative impulse (+12.4% vs. +5.7%), leg spring stiffness (+17.6% vs. +4.6%), contact time (CT) (-10.1% vs. -1.5%), and reactive strength index (+7.2% vs. +2.1%); all comparisons with p = 0.05. Conversely, the HDJ regimen was able to improve the short-distance and COD performances by increasing the step length (+3.5% vs. +1.5% with p = 0.05) and reducing the CT on COD (-12.1% vs. -2.1% with p = 0.05) more than the VDJ. This investigation showed the crucial role that specific plyometric regimens play in optimizing similar biomechanical featured functional performances, such as jumping, sprinting, and COD.